Factor Analysis of Inhibitors to Uptake of Information and Communication Technology for Teaching and Learning Among Pre-Service Teachers in the University - A. T, Shittu,; R., Bello; A. A, Gambaki, (Kashere Journal of Education, 2021)
The concern of this study resides in establishing the inhibitors to uptake of ICT for teaching and learning among pre-service teacher in a university in Nigeria. The study adopted quantitative research approach and of survey type. The final year students of faculty of education constituted the sample of the study. In all, two hundred and two (202) students were purposively used as sample for the study. An adapted and modify questionnaires was used for gathering the data of the study. Prior to the administration of the instrument it was subjected to pilot testing to ascertain its psychometric properties. The reliability of the instrument was established through Cronbach alpha analysis that yielded .82 coefficients. Three research questions were raised to guide the study. The data of the study was subjected to series of analysis including descriptive and factor analysis. The finding showed that there are three major underlying factors that constitute inhibitors to uptake of ICT for teaching among pre-service teachers. Each of the factors contributes to 34%, 19% and 2% variance explained on the each of the three underlined dimension. The factors are embedded in attitudinal and school related factors. The study reported the implications of the findings for the university administrator, teachers’ educator and lecturers..